2020
DOI: 10.1111/mec.15606
|View full text |Cite
|
Sign up to set email alerts
|

Instability of natural selection at candidate barrier loci underlying speciation in wood ants

Abstract: New species are formed when populations become reproductively isolated, that is they no longer interbreed or exchange genetic material (Mayr, 1970). However, until complete reproductive isolation has evolved, gene flow may still occur between the diverging lineages. This genetic exchange is usually localized in the genome, with some regions resisting gene flow better than others. Such regions resistant to gene flow are thought to harbour "barrier loci" that can drive the divergence between lineages despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…They proposed that recessive incompatibilities between the genomes of the two species are exposed to selection in haploid males. Subsequent research on this system has revealed instability in the direction of selection on introgressed alleles in males across a ten-year time interval, with introgression recently favored on average in loci where introgression was previously selected against (61). In the tawny crazy ant Nylanderia fulva, males invariably carry the same allele at two out of 12 microsatellite loci, while females are almost always heterozygous at these loci (20).…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that recessive incompatibilities between the genomes of the two species are exposed to selection in haploid males. Subsequent research on this system has revealed instability in the direction of selection on introgressed alleles in males across a ten-year time interval, with introgression recently favored on average in loci where introgression was previously selected against (61). In the tawny crazy ant Nylanderia fulva, males invariably carry the same allele at two out of 12 microsatellite loci, while females are almost always heterozygous at these loci (20).…”
Section: Discussionmentioning
confidence: 99%
“…This population has been characterized as a hybrid between F. aquilonia and F. polyctena using both genetic markers and morphological data (Kulmuni et al, 2010; Seifert, Kulmuni, & Pamilo, 2010). The Långholmen population is a supercolony consisting of two genetic lineages of hybrid origin (R and W; (Kulmuni & Pamilo, 2014; Kulmuni et al, 2010), which show moderate genetic differentiation ( F ST ≈ 0.105, Kulmuni et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…subgenus. Kulmuni et al (2020) assembled a draft genome using poolseq data from a hybrid F. aquilonia × F. polyctena population, but the assembly is highly fragmented (> 300k contigs, N50 < 2 kbp). At a broader phylogenetic scale, among palaearctic Formica species, two genomes are available for the Coptoformica and Serviformica subgenera, respectively F. exsecta (Dhaygude, Nair, Johansson, Wurm, & Sundström, 2019) and F. selysi (Brelsford et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, intrinsic barriers, such as chromosomal rearrangements and genetic incompatibilities can also lead to heterogeneous genomic differentiation (Faria & Navarro, 2010;Navarro, Betran, Barbadilla, & Ruiz, 1997;Kulmuni et al, 2020;Rieseberg, 2001). Intrinsic barriers inhibits allele exchange in such regions and in linked surrounding regions eventually leads to elevated genetic differentiation.…”
Section: Heterogeneous Differentiation Across the Genomementioning
confidence: 99%